The influence of social support on COPD outcomes mediated by depression - Turnier, Leonard (PLoS One, 2021)
BACKGROUND: The purpose of this study was to explore the association between perceived social support and COPD outcomes and to determine whether the associations are mediated by depressive symptoms. METHODS: Subjects with COPD who were enrolled as part of SPIROMICS were included in this analysis. Questionnaires relating to quality of life, symptom burden, and functional status were administered at annual clinic visits for over a 3 year period. In both cross-sectional and longitudinal analyses, we examined the association of social support as measured by the FACIT-F with COPD outcomes. Cross sectional analyses used multivariable linear or logistic regression, adjusting for covariates. For longitudinal analyses, generalized linear mixed models with random intercepts were used. Models were adjusted with and without depressive symptoms and mediation analyses performed. RESULTS: Of the 1831 subjects with COPD, 1779 completed the FACIT- F questionnaire. In adjusted cross-sectional analysis without depressive symptoms, higher perceived social support was associated with better quality of life, well-being, 6 minute walk distance, and less dyspnea. When also adjusting for depressive symptoms, all associations between social support and COPD outcomes were attenuated and no longer statistically significant. Mediation analysis suggested that depressive symptoms explained the majority (> = 85%) of the association between social support and measured COPD outcomes. Results of the longitudinal analysis were consistent with the cross-sectional analyses. There was no association between social support and odds of exacerbations. CONCLUSION: Higher social support was associated with better COPD outcomes across several measures of morbidity including quality of life, respiratory symptoms, and functional status. In addition, these associations were largely attenuated when accounting for depressive symptoms suggesting that the beneficial association of social support with COPD outcomes may be largely mediated by the association between social support and depression. TRIAL REGISTRATION: SPIROMICS was approved by Institutional Review Boards at each center and all participants provided written informed consent (clinicaltrials.gov: NCT01969344).